The Relationship Between Linoleic Acid Intake and Psychological Disorders in Adults - Mohammadi, Sobhan; Keshteli, Ammar Hassanzadeh; Saneei, Parvane; Afshar, Hamid; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2022)
Background: The association between linoleic acid (LA) intake and mental disorders has not been extensively studied in Middle-Eastern populations. We investigated the association between LA intake and prevalence of depression, anxiety, and psychological distress in a large group of Iranian adults. Methods: This cross-sectional study was conducted on 3362 middle-age adults. LA intake was determined through a validated dish-based 106-item semi-quantitative food frequency questionnaire (FFQ). The validated Hospital Anxiety and Depression Scale (HADS) and General Health Questionnaire (GHQ) was used to define psychological disorders. Results: The prevalence of depression, anxiety, and psychological distress among the study population was respectively 28.6, 13.6 and 22.6%. After adjustment for potential confounders, individuals in the top quartile of LA intake had 41% more likely to be depressed compared to those in the bottom quartile (OR=1.41, 95%CI: 1.02-1.95). Stratified analysis by sex revealed that men in the fourth quartile of LA intake, compared to the first quartile, had 80% higher odds of depression, after considering all potential confounders (OR=1.80, 95% CI: 1.01-3.19). More consumption of LA was also associated with higher odds of depression in older adults (OR=2.45, 95% CI: 1.46-4.10), and normal-weight individuals (OR=1.75, 95% CI: 1.13-2.72). Additionally, higher intake of LA was related to 90% higher odds of psychological distress in older participants (OR=1.90, 95% CI: 1.08-3.36). No significant relation was found between LA intake and anxiety. Conclusion: We found that higher intake of LA, as percentage of energy, was positively associated with depression, especially in men, older adults and normal-weight subjects. Higher intake of LA was also related to higher odds of psychological distress in older individuals. More studies, particularly prospective cohorts, are needed to confirm these findings.